Intrinsic Resistance to MEK Inhibition in KRAS Mutant Lung and Colon Cancer through Transcriptional Induction of ERBB3 - Sun, Chong; Hobor, Sebastijan; Bertotti, Andrea; Zecchin, Davide; Huang, Sidong; Galimi, Francesco; Cottino, Francesca; Prahallad, Anirudh; Grernrum, Wipawadee; Tzani, Anna; Schlicker, Andreas; Wessels, Lodewyk F.A.; et al. (Cell reports (Cambridge), 2014)
There are no effective therapies for the ~30% of human malignancies with mutant RAS oncogenes. Using a kinome-centered synthetic lethality screen, we find that suppression of the ERBB3 receptor tyrosine kinase sensitizes KRAS mutant lung and colon cancer cells to MEK inhibitors. We show that MEK inhibition results in MYC-dependent transcriptional upregulation of ERBB3, which is responsible for intrinsic drug resistance. Drugs targeting both EGFR and ERBB2, each capable of forming heterodimers with ERBB3, can reverse unresponsiveness to MEK inhibition by decreasing inhibitory phosphorylation of the proapoptotic proteins BAD and BIM. Moreover, ERBB3 protein level is a biomarker of response to combinatorial treatment. These data suggest a combination strategy for treating KRAS mutant colon and lung cancers and a way to identify the tumors that are most likely to benefit from such combinatorial treatment.